Factors influencing intention to accept location-based mobile advertising among young mobile user segments: a social exchange perspective. (2018) - Heo, Jun; Chang, Chen-Wei
By adopting the notions of social exchange and the unified theory of acceptance and use of technology, this study discusses how young mobile users weigh between benefit and cost (e.g., perceived risk) when determining to accept location-based advertising (LBA). It also examines the role of trust in the process of the information exchange. In addition, this study explores whether young mobile users can be segmented into heterogeneous user groups and the different groups require a unique application of the theoretically-driven factors. An online survey of college students from US universities reveals that benefits of LBA outweigh the perceived risk and that trust plays a key role in increasing LBA acceptance. Results suggest, however, that the determinants may differently influence different mobile user segments: innovative believers and conventional sceptics. The result highlights the importance of crafting marketing messages uniquely for each of the segments. Implications for theories and practitioners using LBA are discussed.